2020
DOI: 10.3390/ma13173859
|View full text |Cite
|
Sign up to set email alerts
|

Electrochromic Performance of V2O5 Thin Films Grown by Spray Pyrolysis

Abstract: A new approach regarding the development of nanostructured V2O5 electrochromic thin films at low temperature (250 °C), using air-carrier spray deposition and ammonium metavanadate in water as precursor is presented. The obtained V2O5 films were characterized by X-ray diffraction, scanning electron microscopy and Raman spectroscopy, while their electrochromic response was studied using UV-vis absorption spectroscopy and cyclic voltammetry. The study showed that this simple, cost effective, suitable for large ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…Previous studies using conducting polymers for ECD have operated electro-polymerization for preparing EC conducting polymer films, they are not suitable for fabricating large-area coatings. Other preparation methods for EC materials, such as "vacuum sputtering", 19 "chemical bath deposition", 20 "sol−gel process", 21 "pulse laser deposition", 22 and "spray Pyrolysis", 23 have been investigated to improve electrochromic devices. Although a good electrochromic performance, these processes for EC films should overcome the requirement for high temperature conditions to manufacture large-area devices.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies using conducting polymers for ECD have operated electro-polymerization for preparing EC conducting polymer films, they are not suitable for fabricating large-area coatings. Other preparation methods for EC materials, such as "vacuum sputtering", 19 "chemical bath deposition", 20 "sol−gel process", 21 "pulse laser deposition", 22 and "spray Pyrolysis", 23 have been investigated to improve electrochromic devices. Although a good electrochromic performance, these processes for EC films should overcome the requirement for high temperature conditions to manufacture large-area devices.…”
Section: Introductionmentioning
confidence: 99%
“…The calculated values of coloration efficiency are in good agreement with the literature reports. [12,58] [59] In addition, the radio frequency magnetron sputter-deposited Nb 2 O 5 films showed the coloration efficiency of 53 cm 2 C À1 . [60] Furthermore, the η of 77 cm 2 C À1 was reported for V 2 O 5 films deposited by dip coating technique.…”
Section: Chronocoulometry Studymentioning
confidence: 99%
“…The calculated values of coloration efficiency are in good agreement with the literature reports. [12,58] Table 4 shows the comparison of coloration efficiency of various electrochromic materials along with V 2 O 5 films available in the literature. Interestingly, it is observed that the V 2 O 5 films prepared in the current work have highest coloration efficiency compared with other reports.…”
Section: Chronocoulometry Studymentioning
confidence: 99%
See 1 more Smart Citation
“…This process can result in materials with enhanced electrochemical performance for electrochromic applications combined in layered and composite forms for higher reflective property, electrochemical stability and faster electrochromic response [12,13]. In Mouratis et al's letter [14], a new approach regarding the development of V 2 O 5 electrochromic thin films at 250 • C using ammonium metavanadate in water as precursor is shown. The precursor concentration can affect the morphology of the oxides, resulting in a large active surface area suitable for electrochromic applications.…”
mentioning
confidence: 99%